2013
DOI: 10.1111/syen.12023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of fungus gnats (Diptera: Mycetophilidae) revisited: position of Manotinae, Metanepsiini, and other enigmatic taxa as inferred from multigene analysis

Abstract: The phylogeny of selected genera from four subfamilies of fungus gnats (Diptera: Mycetophilidae) – Manotinae, Leiinae, Sciophilinae and Gnoristinae (including Metanepsiini) – is reconstructed based on the combined analysis of five mitochondrial (12S, 16S, COI, COII, cytB) and two nuclear (28S, ITS2) gene markers. Results of the different analyses all support Manotinae as a monophyletic group, with Leiinae as the sister group. Allactoneura DeMeijere is nested in the monophyletic and strongly supported clade of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…The comparison of the three regions sequenced from two genes revealed that the variation in the barcoding region of COI was slightly higher than in the following stretch of comparable length. The latter has been widely used in taxonomic studies on fungus gnats, focusing on higher taxonomic levels (Rindal et al 2009, Ševčík et al 2013). Here we showed its applicability also for species discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the three regions sequenced from two genes revealed that the variation in the barcoding region of COI was slightly higher than in the following stretch of comparable length. The latter has been widely used in taxonomic studies on fungus gnats, focusing on higher taxonomic levels (Rindal et al 2009, Ševčík et al 2013). Here we showed its applicability also for species discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, molecular approaches became the focus of Sciaroidea researchers, which seems natural considering that new characters are needed to advance the phylogenetic discussion and that the rapid development of molecular methods has raised great expectations. Molecular approaches have only recently been applied to phylogenetic studies of Bibionomorpha, but these studies focused either on certain subtaxa (e.g., Rindal, Søli & Bachmann, 2009; Ševčík, Kaspřák & Tóthová, 2013; Ševčík et al, 2014; Shin et al, 2013) or had a major focus beyond the infraorder (Bertone, Courtney & Wiegmann, 2008; Wiegmann et al, 2011; Beckenbach, 2012). As a consequence, taxon sampling was not adjusted to tackle the issues specific to Bibionomorpha.…”
Section: Introductionmentioning
confidence: 99%
“…Rokas et al 2002, Wilkerson et al 2004, Haarto and Ståhls 2014). While COI has successfully been used in studies on fungus gnat taxonomy (Martinsson et al 2011, Rindal et al 2009b, Ševčík et al 2013, 2014) and ecology (Põldmaa et al 2015), ITS2 has been incorporated only in a few studies (Ševčík et al 2013, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Though in recent years nucleotide data have been implemented to address the phylogeny of this group (e.g. Rindal et al 2009a, 2009b, Ševčík et al 2013, 2014), to associate sexes of one species (Kurina et al 2011) and in population genetic studies (Dörge et al 2014). Hippa and Ševčík (2014) provided mitochondrial 12S and 16S sequences in the description of Nepaletricha sigma .…”
Section: Introductionmentioning
confidence: 99%